(untitled) (Bangladesh Journal of Medical Education, 2014)
Background Medical education in Bangladesh is poorly assessed and there is a general lack of documented knowledge about the challenges facing this field and the needs for its development. This study aimed to assess the need of medical education training or course for the teachers of medical colleges. Methods A quantitative study based on a self-administered questionnaire of a purposive sample of 204 teachers of different medical colleges was conducted from 1st July, 2011 to 30th June 2012 to explore their views regarding the training or course in medical education. Results The study revealed that majority (98.5%) of respondents showed their interest for training or course on medical education. Among them 61% preferred a regular course, 29% desired for training program and 10% for refresher training on medical education. Most of the respondents (68%) agreed that there are some barriers to participate in a training or course on medical education. Conclusions The existing medical education system face significant problems and it needs important and comprehensive improvements in or course on medical education. There is a need for further research in this field to explore the identified problems in a more in-depth manner in order to better understand of the problems and needs of training or course on medical education. DOI: http://dx.doi.org/10.3329/bjme.v2i2.18135 Bangladesh Journal of Medical Education Vol.2(2) 2011: 7-11